Biotechnology for the Production of Scutellaria baicalensis Georgi. Plant Material and its Pharmacognostic Analysis. Issue 1 (January 2021) - Tikhomirova, L I; Lisenko, R C
Abstract: The paper describes a technique for micropropagation of S. baicalensis . It implies the use of seeds as primary explants, reproduction of an actively proliferating culture on an MS medium containing 1.0-0.5 μM kinetin and 0.25 μM IBA (indole-3-butyric acid) and 0.05 μM GA (gibberellic acid), rooting of shoots on a medium containing 1 μM IBA. A microscopic analysis of Baikal skullcap ( Scutellaria baicalensis) grown in a tissue culture made it possible to establish the following diagnostic signs: - for the leaf – diacytic stomatal complex, simple warty hairs and capitate hairs; essential oil glands with 4.6 and 8 excretory cells; - for the stem – simple warty and capitate hairs, prosenchyme cells in the epidermis. Biologically active substances of 70% ethanol extracts from progeny plants were screened. Tanins, xanthones, flavonoids and other phenolic compounds were found to be present. A quantitative analysis of some biologically active substances made it possible to obtain the following data: the content of extractives amounted to 12.50±1.03%, with the tannins to make up 8.25±0.62% and a total of flavonoids to be in the range of 5.8±0.2%. For the first time, the content of xanthones was determined in progeny plants of S. baicalensis in terms of mangiferin to be 48±0.01% per ADM.